2009
DOI: 10.1007/s11414-009-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

School Personnel Perspectives on their School’s Implementation of a School-Based Suicide Prevention Program

Abstract: Youth suicide is a national public health priority, with policymakers highlighting schools as an ideal setting in which to deliver suicide prevention programs. Over the past decade, the number of schools implementing such programs has grown substantially, yet little is known about how successfully such programs are being implemented. This study examines the implementation of a district-wide suicide prevention program through key informant interviews with school personnel. Schools with higher rates of implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Gatekeepers are the adults, such as teachers and school counselors, who are in a position to observe and intervene with at-risk adolescents. Gatekeeper training focuses on increasing the identification and response skills of these professionals; subsequent self-reports from those who have received training indicate using the new skills and an increase in referrals (Stein et al, 2010). According to Kalafat (2006), there are several gatekeeper training programs available such as Question Persuade Refer (QPR), Living Works, and Suicide Options and Relief (SOAR).…”
Section: High School Suicide Prevention Programsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gatekeepers are the adults, such as teachers and school counselors, who are in a position to observe and intervene with at-risk adolescents. Gatekeeper training focuses on increasing the identification and response skills of these professionals; subsequent self-reports from those who have received training indicate using the new skills and an increase in referrals (Stein et al, 2010). According to Kalafat (2006), there are several gatekeeper training programs available such as Question Persuade Refer (QPR), Living Works, and Suicide Options and Relief (SOAR).…”
Section: High School Suicide Prevention Programsmentioning
confidence: 99%
“…The authors concluded that the program was effective in equipping these individuals with the necessary skills when refresher courses were utilized and when there were legislative mandates, proper infrastructure, and administrative capacity to sustain the program. Stein et al (2010) evaluated the Los Angeles Unified School District's Youth Suicide Prevention Program (LAUSD) and concluded similarly that excellent administration and communication from the district down to the school, support of leadership (especially the principal), and established resources and channels for referrals were essential to successful training in this gatekeeper program servicing over 740,000 students.…”
Section: High School Suicide Prevention Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas in a study of health education teachers only a quarter felt that if they talked to parents it would reduce the risk of suicide (27%) (King et al 1999). Conversely, where staff are informed about and have access to an organized system with transparent processes for responding effectively to a student who is at risk, self-efficacy of staff has been found to be higher (Anderson 2004;King et al 1999) and more effective responses have been demonstrated (Stein, Kataoka, Hamilton, Schultz, Ryan, Vona & Wong 2010). However, it is known that in many contexts, there is a lack of readily available, responsive mental health Other contextual factors may differ, such as protocols for communication between schools and families.…”
Section: Introductionmentioning
confidence: 99%